Using individual tractor wheel drive through electric traction - А. V. Bizhaev; S. M. Vetrova; A. S. Barchukova; N. S. Krivyh (Сельскохозяйственные машины и технологии, 2024)
In agriculture, tractors serve as the principal machinery for performing traction and driving operations. They are mainly powered by diesel engines with an efficiency of about 40 percent. Electric motors boast an efficiency of 95 percent, presenting the opportunity to serve as independent drives for tractor wheels. The study review existing individual wheel drive systems, revealing operational efficiency improvements of up to 20 percent. A comparative analysis was conducted between tractors using traditional power units and those equipped with electric drive systems. The study also examined factors affecting tractor traction and explored methods to enhance the traction capabilities of these vehicles. (Research purpose) The study aims to evaluate the feasibility of using electric traction for individual drive systems in tractor wheels. (Materials and methods) A concept for controlling individual wheel drives has been developed, as well as an algorithm specifically for managing electric wheels. Additionally, a method has been proposed for detecting slippage, which triggers the switching of the electric wheel drive to the appropriate mode. Furthermore, a new indicator, the «slip factor,» has been introduced to correlate slip with adhesion coefficients. The value of this parameter is used as a criterion for transitioning the electric drive to a different operational mode. (Results and discussion) Traction tests were conducted on the MTZ-82.1 tractor across various supporting surfaces. The measured slip factors were as follows: 0.71 for a cropped field, 0.86 for stubble, 1.19 for fallow land, and 1.74 for asphalt pavement. To accurately assess the wheel’s performance under real conditions, torque measurements were taken using a specialized locking device. These measurements revealed angular displacements of the shaft by 0.2 degrees when subjected to a tangential traction force of 3 kilonewtons on the wheel. (Conclusions) The slip factor for the MTZ-82.1 tractor has been determined. A mathematical model has been proposed that links the wheel’s adhesion properties with slipping. The model proves to be applicable up to a slip limit of 30 percent. This multifactorial approach enables the creation of an adaptive program to enhance wheel efficiency. Additionally, the capability to measure wheel torque has been established.